Red de Conocimiento de Turismo Rural del INTA - Guastavino, Marina; Haag, Maria Isabel; Pérez Winter, Cecilia; Rodil, Diego; Walter, Pablo (Facultad de Ciencias Agrarias, Universidad Nacional de Rosario, 2022)
Ponencia y presentación